Communion without Baptism and the Paradox of the Cross. Issue 3 (June 2020) - Bowman, Hannah
Communion without baptism remains a controversial topic in The Episcopal Church, with many parishes practicing it in violation of the canons of the church. Drawing on recent scholarly arguments both for and against the practice of opening the table to all comers, this article brings a new perspective to the discourse, emphasizing the real presence of Christ in the Eucharist to suggest a way of interpreting the "open table" as an audacious proclamation of the scandalous nature of the gospel of Christ crucified. The cross of Christ, as the reality underlying the eucharistic sacrament, provides a way out of the controversy concerning the practice of open communion.